Alkaloids : a treasury of poisons and medicines - Funayama, Shinji, 1951-; Cordell, Geoffrey A. (Academic Press, 2015)
Alkaloids are a large group of structurally complex natural products displaying a wide range of biological activities. The purpose of Alkaloids: A Treasury of Poisons and Medicines is to classify, for the first time, the alkaloids isolated from the natural sources until now. The book classifies all of the alkaloids by their biosynthetic origins. Of interest to the organic chemistry and medicinal chemistry communities involved in drug discovery and development, this book describes many alkaloids isolated from the medicinal plants, including those used in Japanese Kampo medicine. Classifies and l.